2006
DOI: 10.1016/j.jacc.2006.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Effects of Inhaled Treprostinil in Severe Pulmonary Hypertension

Abstract: Inhaled treprostinil exerts sustained pulmonary vasodilation with excellent tolerability at relatively low doses and may be inhaled in a few breaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 16 publications
2
84
0
2
Order By: Relevance
“…In preceding studies we found that quite high doses of inhaled treprostinil could be safely deposited in the lung in as little as a single breath [8]. This suggested for the first time the possibility to deliver a potent vasodilator for pulmonary hypertension treatment with a metered dose inhaler.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…In preceding studies we found that quite high doses of inhaled treprostinil could be safely deposited in the lung in as little as a single breath [8]. This suggested for the first time the possibility to deliver a potent vasodilator for pulmonary hypertension treatment with a metered dose inhaler.…”
Section: Introductionmentioning
confidence: 81%
“…It was an unanticipated finding that treprostinil, besides the positive consequences of a longer half life for inhalation therapy, was tolerated at single doses up to 60µg without relevant side effects. The inhalation of an effective treprostinil dose in one single breath was achieved with highly concentrated treprostinil sodium solution of 2000µg/ml without side effects [8]. We believe that the absence of systemic side effects despite rapid application of treprostinil in high doses is…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…or s.c. administration [34] or inhalation [35]. Several studies that included both older children and adults demonstrated or suggested efficacy of treprostinil i.v.…”
Section: Treprostinilmentioning
confidence: 99%